Aplicabilidade de análise de falhas no setor de manutenção - Rodrigues, Luiz Alberto (2016)
In modern maintenance, we still find the strategy of servicing correctively. Such maintenance model is still employed due to their short-term profitability, as compared to preventive maintenance or predictive, at a higher level; corrective maintenance does not require a large availability of financial resources of the company. But the charts in a production line due to unscheduled maintenance, entail a specific cost as the people involved in the production are available to the company, in the company is paying the employee without the same being producing. In an ideal scenario maintenance, there is a differentiation of equipment for a degree of criticism, and that is the critical one should define a maintenance strategy through a maintenance model. Even using corrective maintenance as part of the system, these, however, should be recorded and controlled, known by technician and managers. To study a break or even repeats of short breaks in production, some quality tools are applicable. The applicability of these tools can be measured through performance indicators, where through these; you can define strategies for a controlled management system.